2018
DOI: 10.1371/journal.pbio.2006192
|View full text |Cite
|
Sign up to set email alerts
|

Insight into small molecule binding to the neonatal Fc receptor by X-ray crystallography and 100 kHz magic-angle-spinning NMR

Abstract: Aiming at the design of an allosteric modulator of the neonatal Fc receptor (FcRn)–Immunoglobulin G (IgG) interaction, we developed a new methodology including NMR fragment screening, X-ray crystallography, and magic-angle-spinning (MAS) NMR at 100 kHz after sedimentation, exploiting very fast spinning of the nondeuterated soluble 42 kDa receptor construct to obtain resolved proton-detected 2D and 3D NMR spectra. FcRn plays a crucial role in regulation of IgG and serum albumin catabolism. It is a clinically va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…Sample preparation by sedimentation allowed for the investigation of proteins that are difficult (or even impossible) to crystallize. Theoretically, the molecular mass of the protein determines the success of sedimentation, and proteins, such as the RNA polymerase subunits Rpo4/7 * (the * indicates that the Rpo7 unit is uniformly 13 C/ 15 N labeled) with a molecular weight of 34 kDa (Torosyan et al, 2019), the pRN1 primase with 40 kDa (Boudet et al, 2019), the neonatal Fc receptor with 40 kDa (Stöppler et al, 2018) as well as the human superoxide dismutase with 32 kDa (Fragai et al, 2013), the bacterial helicase DnaB with 708 kDa (Gardiennet et al, 2012), the iron-storage protein ferritin with 480 kDa (Bertini et al, 2012), a variety of supramolecular assemblies (Lecoq et al, 2018;Gauto et al, 2019), and PEGylated proteins (Ravera et al, 2016), were shown to form sediments suitable for solid-state NMR. This is for some of these systems probably a consequence of oligomerization that has been induced by the high protein concentrations (Bertini et al, 2013;Fragai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample preparation by sedimentation allowed for the investigation of proteins that are difficult (or even impossible) to crystallize. Theoretically, the molecular mass of the protein determines the success of sedimentation, and proteins, such as the RNA polymerase subunits Rpo4/7 * (the * indicates that the Rpo7 unit is uniformly 13 C/ 15 N labeled) with a molecular weight of 34 kDa (Torosyan et al, 2019), the pRN1 primase with 40 kDa (Boudet et al, 2019), the neonatal Fc receptor with 40 kDa (Stöppler et al, 2018) as well as the human superoxide dismutase with 32 kDa (Fragai et al, 2013), the bacterial helicase DnaB with 708 kDa (Gardiennet et al, 2012), the iron-storage protein ferritin with 480 kDa (Bertini et al, 2012), a variety of supramolecular assemblies (Lecoq et al, 2018;Gauto et al, 2019), and PEGylated proteins (Ravera et al, 2016), were shown to form sediments suitable for solid-state NMR. This is for some of these systems probably a consequence of oligomerization that has been induced by the high protein concentrations (Bertini et al, 2013;Fragai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Protein-protein complexes were studied by co-sedimentation (Gardiennet et al, 2016;Xiang et al, 2018) and protein-ligand complexes by sedimentation with the respective ligand (e.g. nucleic acids) directly into the NMR rotor (Wiegand et al, 2016a;Kaur et al, 2018;Stöppler et al, 2018;Lacabanne et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions have been typicallys tudied in the past by high-resolution X-ray crystallography. [14][15][16][17][18][19][20][21][22][23] Proton chemical-shift values are highly sensitivet oh ydrogen bonding [24][25][26][27] as shown in theoretical, [26,27] buta lso in experimental studies. [8] And indeed, solid-state NMR spectroscopy has been used to identify residues at protein-RNA interfaces in smaller proteins.…”
mentioning
confidence: 96%
“…[9] Intermolecular information can also be obtained from 31 P-detected, heteronuclear correlation experimentsp robingt he spatial proximity of nucleotide 31 Pa nd protein 15 No r 13 Cn uclei. [14][15][16][17][18][19][20][21][22][23] Proton chemical-shift values are highly sensitivet oh ydrogen bonding [24][25][26][27] as shown in theoretical, [26,27] buta lso in experimental studies. [14][15][16][17][18][19][20][21][22][23] Proton chemical-shift values are highly sensitivet oh ydrogen bonding [24][25][26][27] as shown in theoretical, [26,27] buta lso in experimental studies.…”
mentioning
confidence: 96%
“…Continuous technological and conceptual developments have endowed contemporary high‐resolution solid‐state nuclear magnetic resonance (NMR) spectroscopy, with capabilities that rival those of solution‐state NMR when tackling structural and dynamic investigations of large biomolecules . When performing such studies the problem of spectral assignment and resolution nearly invariably arises, demanding the use of high‐dimensional NMR experiments correlating labeled 13 C‐ and/or 15 N sites in the biomolecule.…”
Section: Introductionmentioning
confidence: 99%